An Agrarian Republic : Farming, Antislavery Politics, and Nature Parks in the Civil War Era - Dean, Adam Wesley (Book collections on Project MUSE., 2015)
"The familiar story of the Civil War tells of an agrarian South pitted against a rapidly industrializing North. However, Adam W. Dean argues that the political ideology of the triumphant Republican Party was fundamentally agrarian. Believing small farms owned by families for generations led to a model society, Republicans saw slavery as a foil to the northern agricultural ideal. In their view, plantation agriculture destroyed the land's productivity, required constant western expansion, and produced an elite landed gentry hostile to the Union. Dean shows how, over time, these ideas shaped the debate over slavery's expansion, spurred the creation of the Department of Agriculture and the passage of the Homestead Act, and laid a foundation for the development of conservation ideas that supported the creation of the earliest national parks"--Provided by publisher